(untitled) (Research, Society and Development, 2021)
Objectives: This study evaluated, through histological and immunohistochemical analysis the bone formation and remodeling after a maxillary sinus lift. Material and methods: 25 patients from 41 to 65 years of age, with inadequate bone volume in the posterior maxillary region and remaining native bone less than or equal to 5 mm, as measured radiographically, were selected and underwent maxillary sinus lift surgery, through the open technique. They were distributed in 3 groups: A - particulate, autogenous bone, AB - autogenous and heterogeneous bone, and B - only heterogeneous bone. Six months after this intervention, the patients were submitted to a surgery for the installation of implants and concomitant removal of the grafted bone sample from the surgical site. Results: The histological evaluation showed bone formation in the three groups, with presence of mature bone. In groups B and AB, the presence of granules of the biomaterial surrounded by bone tissue was observed. A statistical analysis showed significant difference (ANOVA p=0,002), suggesting greater bone formation in the autogenous group. In an immunohistochemical evaluation, no statistically significant differences were observed in the comparison between the experimental groups (A, B and AB), as well as in the proteins analyzed (OC: p= 0.657; VEGF: p= 0,133; TRAP: p= 0.163). Conclusion: The use of Bio-Oss ®, whether or not associated to autogenous bone, for a maxillary sinus lift through the side window technique results in bone repair. A predictable amount of bone formation is attained when this osteoconductive biomaterial is used.